Epidemiology of Chlamydia psittaci infections in pregnant Thoroughbred mares and foals. (July 2021) - Anstey, S.; Lizárraga, D.; Nyari, S.; Chalmers, G.; Carrick, J.; Chicken, C.; Jenkins, C.; Perkins, N.; Timms, P.; Jelocnik, M.
Highlights: Longitudinal study followed pregnant Thoroughbred mares and foals from 14 studs. C. psittaci equine abortions can occur sporadically every foaling season. Healthy newborn foals tested positive to C. psittaci with no clinical disease. Abortion cases correlated with 'avian' C. psittaci genotype and with frost events. C. psittaci should be routinely tested for in equine abortion cases. Abstract: Late-term foal loss due to the traditional avian pathogen Chlamydia psittaci recently emerged as a threat to the Australian Thoroughbred industry. A longitudinal study of 14 stud farms was undertaken to better understand C. psittaci infection in pregnant mares and their foals by evaluating C. psittaci prevalence, equine herpesvirus-1 (EHV-1) co-infection, avian reservoirs, and potential risk factors. Mucosal swabs taken from 228 healthy pregnant mares and their foals were tested for C. psittaci and EHV-1 using species-specific qPCR assays. No foal loss was recorded due to either pathogen, and no mare tested positive to either C. psittaci or EHV-1. However, healthy newborn foals tested positive to both pathogens, at low levels, with 13.2% ( n = 30/228) and 14.5% ( n = 33/228) prevalence for C. psittaci and EHV-1, respectively. Co-infection occurred in 1.3% ( n = 3/228) of foals. In avian environmental faecal samples collected from the same studs, C. psittaci was detected at 5.3% ( n = 5/94). Multiple logistic regression modelling found that foals born in winter were more likely to be infected with C. psittaci (adjusted odds ratio = 15.83; P < 0.001; Confidence Interval 5.12–48.49). Being a maiden mare, absence of prophylactic vaginal suture, interventions in the last trimester and residing on a farm with prior history of C. psittaci abortion posed no higher risk to infection in the newborn. Analysis of all reported C. psittaci abortion cases (Hunter Valley, 2016–2019) revealed a dominant C. psittaci sequence type (denoted ST24) and a significant correlation with frost events (Spearmans' rho = 0.44; P = 0.002).